Online Support for Education in Entrepreneurial and Intrapreneurial Competences: A Proposal for an Assessment Tool and Support for Tailor-Made Training - Jaume Teodoro; Ester Bernadó; Florian Bratzke; Anita Zehrer; Wouter Van Bockhaven (MDPI AG, 2022)
Higher education institutions across Europe are called to offer entrepreneurship education. Despite the rising interest and the increased offerings in the last decades, entrepreneurship education is yet not as mature as other disciplines, and it is still underdeveloped in some faculties and institutions. One way of embedding entrepreneurship education within different disciplines is to take a broader approach beyond teaching how to start up and focusing on developing the entrepreneurial competences of students, which equip them to provide value to society (either economic, social, or cultural). This article describes an online platform-named EICAA-that supports educators and trainers aiming at teaching/guiding/coaching students or employees in developing entre/intrapreneurial competences. The platform is based on a Competence Framework built upon a systematic literature review, which defines 18 key competences grouped in three competence areas. The platform allows the educator to assess the entrepreneurial competences of a group of students/participants, via the so-called Competence Monitor and provides tailor-made training with the Competence Development Kit. The platform is being used in five European universities and is open to be used by any higher education institution or organisation aiming at developing the entrepreneurial competences of their students and/or employees. Future developments of the tool can be enriched from the experiences of the participant institutions and could become an open collaborative online tool.